'Feeling a bit like a tsunami wave': an exploratory study of early childhood professionals' experiences during the COVID-19 crisis in the USA. Issue 2 (17th February 2023) - Shin, Minsun; Puig, Victoria I.
ABSTRACT: The COVID-19 crisis highlights how vital childcare is and demonstrates the importance of the often undervalued work of early childhood educators. This mixed methods exploratory study presents how early childhood professionals ( n = 75) navigated alternate remote teaching formats and served young children and their families during the COVID-19 crisis in the U.S. Key findings include the personal and professional challenges participants experienced supporting their students' social-emotional development and serving children with disabilities. Participants also shared reflections on the resilience and adaptability of children, families, and themselves. Recommendations for interdisciplinary research, professional development that builds technological proficiency, and practice that supports children and families through inclusive early childhood models are discussed.